Studi Identifikasi dan Proyeksi Siklus Harga Komoditas Pangan di Masa Pandemi COVID 19 sebagai Kajian Aspek Pengawasan Pemasaran Produk Pangan di Bangka Belitung: Study on Identification and Projection of Food Commodity Price Cycles during the COVID-19 Pandemic Period as a Study of Supervision Aspects of Food Product Marketing in Bangka Belitung - Muhammad Faisal Akbar; Izma Fahria (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2022)
This study examined the projected price of food marketing in the Province of the Bangka Belitung Islands as a step in deepening the issue of food security due to the COVID-19 pandemic. The COVID-19 pandemic in the Province of the Bangka Belitung Islands had a significant impact on the issue of food security. This was caused by the deficit of several strategic food commodities and caused the prices of this food to increase quite high compared to other provinces in Indonesia, such as several provinces in Sumatra and Java. Therefore, local governments as policymakers have a high enough interest in maintaining prices for strategic commodities, especially food. This study intends to compare the volatility of food prices before and after the COVID-19 pandemic. The data used is time-series data on weekly food prices in a traditional Pangkalpinang City market for September 2018 to February 2021. The data analysis technique uses the Vector Autoregression (VAR) method or Vector Error Correction Model (VECM) with the help of statistical software EViews. The results of this study indicate that several important commodities that support community life are predicted to increase significantly, including rice, chicken meat, and chicken eggs. The three food commodities that experienced an increase had a fairly high fluctuation. Beef and red chilies show declining projections in the 8-week forecast period. Meanwhile, cooking oil prices, granulated sugar, shallots, and garlic are still stable.